Team teaching during field experiences in teacher education: Exploring the assistant teaching model. Issue 3 (27th May 2018) - Baeten, Marlies; Simons, Mathea; Schelfhout, Wouter; Pinxten, Rianne
Abstract: Teacher education institutes are in search of alternative models of field experiences, inspired by collaborative learning. This study examines team teaching. We focus upon the assistant teaching model, in which the student teacher assists the mentor during teaching. We investigate which assisting activities student teachers prefer, how student teachers and mentors experience these activities and the conditions for implementation they foresee. Data were gathered using activity reports, reflective documents and questionnaires. Results show that the preferred assisting activities mainly consist of guiding pupils during individual and team work and of teaching a part of a lesson in front of an entire class group. The assistant teaching model has both advantages (professional growth, …) and disadvantages (feelings of unfamiliarity, …) for the student teacher. Advantages and disadvantages have also been reported for mentors (support, high workload, …) and pupils (support, confusion, …). Finally, several conditions for successful implementation of the assistant teacher model are discussed.